The Role of Protein Intake: Benefits, Risks, and Metabolic Effects – A Literature Review - Jakubowska, Paulina; Szaryński, Mikołaj; Jakubowska, Martyna; Gólcz, Julia; Sikorski, Adam; Bursztyn, Michał; Gólcz, Adrian; Kadłubowska, Karolina; Chojnowska, Natalia; Rytel, Jan; et al. (Quality in Sport, 2026)
This work is a literature review examining the effects of dietary protein intake on muscle strength, body composition, metabolic health, hormonal regulation, and gastrointestinal function in healthy adults, including athletes. The review covers studies on moderate and high protein intake from various sources and considers differences related to age, training level, and macronutrient balance. Research shows that higher protein intake supports increases in lean body mass and lower-body strength, especially in resistance-trained and older adults consuming at least 1.6 g/kg/day. During caloric restriction, increased protein intake helps preserve muscle mass in overweight and obese individuals. Very high protein intake above 3.4 g/kg/day may reduce testosterone levels in men, whereas moderate intakes do not produce hormonal disturbances. Protein source influences metabolic outcomes: animal and seafood protein intake is linked to a higher risk of hyperuricemia, while plant proteins, particularly soy, show protective effects. The impact of protein intake on gut function depends on carbohydrate availability, with high-protein, low-carbohydrate diets increasing constipation risk. Studies also show wide variability in dietary protein intake among athletes, emphasizing the need for individualized nutrition strategies. Overall, the review concludes that optimal protein intake depends on training type, age, diet composition, and protein quality. High-protein diets generally support muscle health and metabolic function, but the long-term consequences of very high protein intake require further study.